The Subtextual Hope of Possibility in Keiichi Okabe's Weight of the World (Kowareta Sekai No Uta) - Rommel Utungga Pasopati; Michelle Michelle; Riska Dewi Ramadhani; Dwi Ainur Riza; Khaled Ahmed Mohammed (Universitas Diponegoro, 2025)
This paper explores the idea of hope of possibility in Keiichi Okabe’s song entitled Weight of the World or translated as Kowareta Sekai No Uta. In the game called NieR: Automata, the song is a cry of a girl who wants to save everyone from anything bad that happened to them. She wanted to redeem her past mistakes by praying the God to help her through dark times, even though the opportunity that she got is unknown. Then, how is the hope of possibility asserted in Keiichi Okabe’s Weight of the World? Through qualitative method and explorative approach, this writing explains the possibility of hope retaining the girl to achieve her dream through the unknown probability. Supported by the theory of Adrienne M. Martin, the concept extended the orthodox view of hope with the girl’s incorporation elements in this song. This is also interrelated with the human condition, highlighting how individual aspirations contribute to collective resilience and transformation. By understanding hope as a multifaceted concept, this paper underscores the complexity of human existence and the potential for renewal within shared struggles. In conclusion, the hope exists in her journey as any unknown possibility to save everyone is answered. <a href=